Diabetes - diagnosis, treatment, complications and rehabilitation - Lipka, Marta; Kończalska, Karolina; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2020)
<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: bold; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Introduction:<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> Diabetes mellitus is a disease that cannot be completely cured, but by following the recommendations of Healthcare professionals, it is possible to maintain good health for a long time. The most important thing during treatment is to normalize the glucose level and maintain a balanced diet. The aim of the study is to present the problem of diabetes, to present the causes and effects of the disease, and to describe rehabilitation after its complications. <span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: bold; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Results:<span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">In Poland, more than 2.9 million people are ill and the disease curve is constantly growing. Scientists predict that in a few dozen years there may be half a billion people in the world. Many people are not aware that this civilization disease also affects them. The reasons may be an inappropriate lifestyle, smoking, obesity, lack of physical activity. Early treatment initiation can prevent serious complications such as retinopathy, nephropathy, and peripheral neuropathy that result in DFU and, consequently, lead to limb amputation. Despite accompanying diabetes for several years, some patients report insufficient knowledge about their disease. Educating patients by doctors about the course of the disease and its treatment is an indispensable element during treatment. This improves the patients' quality of life. <span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: bold; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Conclusion: <span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Diabetes mellitus is a disease that affects a large part of the population and the incidence continues to increase. <span style="font-size: 12pt; font-family: 'Times New Roman'; color: #000000; background-color: #ffffff; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">To counteract disease, you need to measure your blood sugar regularly. Exercise and an appropriate diet will help prevent the disease.